Preparation method of aliphatic diamine furandicarboxylate and crystal thereof
The preparation of aliphatic diamine furan dicarboxylate (PAnF salt) and its crystals in no or small amount of solvents by mechanochemical grinding method, solving the problems of high energy consumption and high production costs in the prior art, and achieving a green, sustainable and efficient preparation process.
Patent Information
- Application Number
- CN202510027120.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-17
- Publication Date
- 2025-04-15
AI Technical Summary
In the prior art, when preparing aliphatic diamine furandicarboxylate (PAnF salt) and its crystals, there are problems such as high energy consumption, multi-solvent use and high production costs.
The PAnF salt and its crystals were prepared without or a small amount of solvent by using mechanochemical grinding method. By grinding a mixture of aliphatic diamine and furandicarboxylic acid, high-purity PAnF salt crystals were crystallized.
A green, sustainable and efficient preparation method is achieved, reducing solvent use and energy consumption, reducing production costs, and improving product purity and stability.
Smart Images

Figure CN119823079A_ABST
Abstract
Description
[0001] The present invention is a divisional application of 2023108737481 2023108737481 filed on July 17, 2023. Technical Field
[0002] The invention belongs to the field of raw material refining of bio-based polymers, and specifically relates to a monomer (raw material) of bio-based nylon nF, aliphatic diamine furandicarboxylate, and a preparation method of its crystal structure. Background Art
[0003] As one of the five major engineering plastics, nylon (polyamide) has good mechanical properties, wear resistance and corrosion resistance, and has a wide range of applications. With the increasing scarcity of global oil resources, facing this unprecedented energy crisis, nylon materials derived from oil raw materials are severely restricted. On the other hand, the excessive industrial utilization of fossil resources has caused environmental pollution, ecological deterioration and other problems. The serious resource, energy and environmental crisis has prompted the world to nurture a major revolution to replace fossil resources with bio-renewable resources, so bio-based nylon materials derived from renewable raw materials have received widespread attention.
[0004] Aliphatic diamines, one of the monomers of nylon nF, can be produced from biomass raw materials. Furandicarboxylic acid is a bio-based aromatic dibasic acid similar to terephthalic acid, which can be produced from biomass-derived 5-hydroxymethylfurfural and has been used in commercial production. Therefore, bio-based nylon nF is a high-performance material with great commercial value.
[0005] Aliphatic diamine is a kind of aliphatic diamine with odor, strong volatility, and easy to absorb acidic carbon dioxide in the air, which brings many difficulties to transportation and storage. The synthesis of nylon is a condensation polymerization reaction. If you want to synthesize a polymer with a larger molecular weight, you need to strictly control the equimolar reaction of dibasic acid and diamine to obtain high-quality polymer materials. However, for liquid aliphatic diamines containing a small amount of impurities and industrial-grade furan dicarboxylic acid, it is difficult to maintain an equimolar ratio during the polymerization process. Usually, the first step in the preparation of polyamide is usually to synthesize the corresponding diamine diacid salt. This salt is a special ionic compound formed by proton exchange between diacid and diamine, which can ensure that the stoichiometric ratio of acid and amine end groups is 1:1 to obtain a high molecular weight polymer. Because nylon salt is in a solid and neutral state, its properties are generally very stable. Salt formation not only improves the purity and stability of the monomer, ensures the molar ratio so that it can be directly used for polymerization, but also changes the product form, eliminates the odor of the raw material amine, makes it easy to transport and use, and has lower storage and transportation costs. Therefore, most condensation polymerization reactions are carried out in the form of nylon salts.
[0006] Existing nylon salts are all prepared in a solution, that is, the acid and the amine are first dissolved in water by heating and then crystallized by adding an organic solvent or cooling. For example, Chinese invention CN105777553A uses water as a solvent solution method to form salts, and then adds organic solvents such as alcohols and lipids for anti-solvent crystallization. For example, Chinese invention CN1887841A dissolves diamine diacids at high temperature and then cools and crystallizes. For example, Chinese invention CN112111058A dissolves them in a solvent under the protection of an inert gas to react to generate nylon salts. For example, Chinese invention CN111925521A heats up the reaction under the action of a catalyst to obtain nylon salts. This process consumes a lot of reagents and energy, which ultimately leads to an increase in production costs.
[0007] Mechanochemical milling is a green, sustainable and efficient method to achieve controlled crystallization results in the field of pharmaceutical cocrystal construction without solvents or with low amounts of solvents. Therefore, mechanochemistry follows the principles of green chemistry, promotes benign reactions, limits the use of solvents, and optimizes all resources involved. Compared with typical solution crystallization, it undoubtedly has higher yields and is more controllable. In addition to this, the obtained product is easy to dry. Summary of the invention
[0008] Purpose of the invention: The technical problem to be solved by the present invention is to provide aliphatic diamine furan dicarboxylate (PAnF salt) and its crystals in view of the deficiencies in the prior art.
[0009] The technical problem that the present invention also solves is to provide a green, sustainable and efficient method for preparing the above-mentioned aliphatic diamine furandicarboxylate (PAnF salt) and its crystals.
[0010] In order to solve the above technical problems, the present invention discloses an aliphatic diamine furan dicarboxylate as shown in Formula I;
[0011]
[0012] n is selected from any integer between 5 and 10, and the crystal structure information is shown in Table 1.
[0013] When n is selected from any integer of 6-9, the tap density / bulk density of the aliphatic diamine furandicarboxylate is 1.0 to 1.25, preferably 1.05 to 1.20.
[0014] Table 1 Six crystal structure information of aliphatic diamine furan dicarboxylate
[0015]
[0016] Wherein, when n=5, the diamine furandicarboxylate is solid pentamethylenediamine furandicarboxylate (PA5F salt), wherein the PA5F salt is a solid salt at a specific temperature formed by combining pentamethylenediamine divalent cations and furandicarboxylic acid divalent anions in a molar ratio of 1:1, and has a molecular formula of C 11 H 18 N2O5.
[0017] The crystal structure of the pentamethylenediamine furandicarboxylate belongs to the monoclinic system, the C2 / c space group, and the unit cell parameters are α=90°, β=100.022(2)°, γ=90°,unit cell volume Z=1 in the unit cell, and its smallest asymmetric unit contains 1 pentamethylenediamine cation and 1 furandicarboxylate anion.
[0018] The minimum asymmetric unit diagram and the unit cell stacking diagram of the pentamethylenediamine furan dicarboxylate are as shown in the attached drawings. Figure 1 and attached Figure 2 It has the following features: Figure 3 The diffraction pattern of the PA5F salt shown in the curve of the diffraction analysis using CuKα rays as characteristic X-rays has the following X-ray powder diffraction characteristic lines measured after grinding according to 2θ±0.1 diffraction angle and 1% relative intensity, measured using Cu-Kα rays:
[0019]
[0020] The PA5F salt crystals and crystalline powders have a bulk density greater than 0.49 g / cm 3 , preferably 0.49-0.52g / cm 3 .
[0021] The PA5F salt crystals and crystalline powders have a tap density greater than 0.64 g / cm 3 , preferably 0.66-0.71 g / cm 3 .
[0022] Wherein, when n=6, the diamine furandicarboxylate is solid hexamethylenediamine furandicarboxylate (PA6F salt), and the PA6F salt is a salt in a solid state at a specific temperature formed by combining hexamethylenediamine divalent cations and furandicarboxylic acid divalent anions in a molar ratio of 1:1, and its molecular formula is C 12 H 20 N2O5.
[0023] The crystal structure of the hexamethylenediamine furan dicarboxylate belongs to the monoclinic system, the P21 / c space group, and the unit cell parameters are α=90°, β=108.538(3)°, γ=90°,unit cell volume Z=4 in the unit cell, and its smallest asymmetric unit contains 1 hexamethylenediamine cation and 1 furandicarboxylate anion.
[0024] The minimum asymmetric unit diagram and the unit cell stacking diagram of the hexamethylenediamine furan dicarboxylate are shown in the attached drawings. Figure 1 and attached Figure 2 It has the following features: Figure 3 The diffraction pattern of the PA6F salt curve shown in the figure is a diffraction analysis using CuKα rays as characteristic X-rays, and has the following X-ray powder diffraction characteristic lines measured after grinding according to 2θ±0.1 diffraction angle and 1% relative intensity, measured using Cu-Kα rays:
[0025]
[0026] The PA6F salt crystals and crystalline powders have a bulk density greater than 0.77 g / cm 3 , preferably 0.82-0.84 g / cm 3 .
[0027] The PA6F salt crystals and crystalline powders have a tap density greater than 0.81 g / cm 3 , preferably 0.88-0.89 g / cm 3 .
[0028] Wherein, when n=7, the diamine furandicarboxylate is solid heptanediamine furandicarboxylate (PA7F salt), wherein the PA7F salt is a solid salt at a specific temperature formed by combining heptanediamine divalent cations and furandicarboxylic acid divalent anions in a molar ratio of 1:1, and has a molecular formula of C 13 H 22 N2O5.
[0029] The crystal structure of the heptanediamine furan dicarboxylate belongs to the monoclinic system, the P21 / c space group, and the unit cell parameters are α=90°, β=105.896(3)°, γ=90°,unit cell volume Z=4 in the unit cell, and its smallest asymmetric unit contains 1 heptanediamine cation and 1 furandicarboxylate anion.
[0030] The minimum asymmetric unit diagram and the unit cell stacking diagram of the heptanediamine furan dicarboxylate are shown in the attached drawings. Figure 1 and attached Figure 2 It has the following features: Figure 3 The diffraction pattern of the PA7F salt shown in the curve of the diffraction analysis using CuKα rays as characteristic X-rays has the following X-ray powder diffraction characteristic lines measured after grinding according to 2θ±0.1 diffraction angle and 1% relative intensity, measured using Cu-Kα rays:
[0031]
[0032] The PA7F salt crystals and crystalline powders have a bulk density greater than 0.44 g / cm 3 , preferably 0.47-0.58 g / cm 3 .
[0033] The PA7F salt crystals and crystalline powders have a tap density greater than 0.50 g / cm 3 , preferably 0.53-0.62 g / cm 3 .
[0034] Wherein, when n=8, the diamine furandicarboxylate is solid octanediamine furandicarboxylate (PA8F salt), wherein the PA8F salt is a salt in a solid state at a specific temperature formed by combining octanediamine divalent cations and furandicarboxylic acid divalent anions in a molar ratio of 1:1, and has a molecular formula of C 14 H 24 N2O5.
[0035] The crystal structure of the octanediamine furan dicarboxylate belongs to the monoclinic system, the C2 / c space group, and the unit cell parameters are α=90°, β=127.238(6)°, γ=90°,unit cell volume Z=4 in the unit cell, and in its smallest asymmetric unit, it contains 0.5 octanediamine cations and 0.5 furandicarboxylate anions.
[0036] The minimum asymmetric unit diagram and the unit cell stacking diagram of the octanediamine furan dicarboxylate are shown in the attached drawings. Figure 1 and attached Figure 2 It has the following features: Figure 3 The diffraction pattern of the PA8F salt shown in the curve of the diffraction analysis using CuKα rays as characteristic X-rays has the following X-ray powder diffraction characteristic lines measured after grinding according to 2θ±0.1 diffraction angle and 1% relative intensity, measured using Cu-Kα rays:
[0037]
[0038] The PA8F salt crystals and crystalline powders have a bulk density greater than 0.25 g / cm 3, preferably 0.25-0.38 g / cm 3 .
[0039] The PA8F salt crystals and crystalline powders have a tap density greater than 0.28 g / cm 3 , preferably 0.30-0.44 g / cm 3 .
[0040] Wherein, when n=9, the diamine furandicarboxylate is a solid nonanediamine furandicarboxylate (PA9F salt), wherein the PA9F salt is a solid salt at a specific temperature formed by combining nonanediamine divalent cations and furandicarboxylic acid divalent anions in a molar ratio of 1:1, and has a molecular formula of C 15 H 26 N2O5.
[0041] The crystal structure of the nonanediamine furandicarboxylate belongs to the monoclinic system, the Cc space group, and the unit cell parameters are α=90°, β=108.924(3)°, γ=90°,unit cell volume Z=1 in the unit cell, and its smallest asymmetric unit contains 4 nonanediamine cations and 4 furandicarboxylate anions.
[0042] The minimum asymmetric unit diagram and the unit cell stacking diagram of the nonanediamine furan dicarboxylate are shown in the attached drawings. Figure 1 and attached Figure 2 It has the following features: Figure 3 The diffraction pattern of the PA9F salt shown in the curve of the diffraction analysis using CuKα rays as characteristic X-rays has the following X-ray powder diffraction characteristic lines measured after grinding according to 2θ±0.1 diffraction angle and 1% relative intensity, measured using Cu-Kα rays:
[0043]
[0044] The PA9F salt crystals and crystalline powders have a bulk density greater than 0.45 g / cm 3 , preferably 0.49-0.6 g / cm 3 .
[0045] The PA9F salt crystals and crystalline powders have a tap density greater than 0.50 g / cm 3 , preferably 0.65-0.66 g / cm 3 .
[0046] Wherein, when n=10, the diamine furandicarboxylate is a solid decanediaminofuran dicarboxylate (PA10F salt), wherein the PA10F salt is a solid salt at a specific temperature formed by combining decanediamin divalent cations and furandicarboxylic acid divalent anions in a molar ratio of 1:1, and has a molecular formula of C 16 H 28 N2O5.
[0047] The minimum asymmetric unit diagram and the unit cell stacking diagram of the decanediamine furan dicarboxylate are as shown in the attached drawings. Figure 1 and attached Figure 2 It has the following features: Figure 3 The diffraction pattern of the PA10F salt shown in the curve of the diffraction analysis using CuKα rays as characteristic X-rays has the following X-ray powder diffraction characteristic lines measured after grinding according to 2θ±0.1 diffraction angle and 1% relative intensity, measured using Cu-Kα rays:
[0048]
[0049] The PA10F salt crystals and crystalline powders have a bulk density greater than 0.52 g / cm 3 , preferably 0.53-0.6 g / cm 3 .
[0050] The PA10F salt crystals and crystalline powders have a tap density greater than 0.72 g / cm 3 , preferably 0.74-0.78 g / cm 3 .
[0051] In order to solve the above second technical problem, the present invention discloses a preparation method of aliphatic diamine furan dicarboxylate as shown in Formula I - a grinding method.
[0052] The grinding method specifically comprises grinding a mixture containing an aliphatic diamine and furandicarboxylic acid to crystallize an aliphatic diamine furandicarboxylic acid salt; separating the salt from the mixture and drying it to obtain;
[0053]
[0054] n is any integer selected from 5-10.
[0055] Wherein, the molar ratio of the aliphatic diamine to furandicarboxylic acid is 1:0.5-1.5. It should be noted that when the aliphatic diamine and furandicarboxylic acid are crystallized in an equimolar ratio, the solid product obtained is more likely to form a crystalline powder of aliphatic diamine furandicarboxylic acid salt with an equimolar ratio of aliphatic diamine cations and furandicarboxylic acid anions. If the total molar number of furandicarboxylic acid added during the crystal preparation process is greater than or less than the molar number of the aliphatic diamine initially added, the solid product obtained is more likely to form the composition of the present invention. Specifically, when the molar number of furandicarboxylic acid added is greater than the molar number of the initial aliphatic diamine, the resulting powder will show weak acidity or acidity; when the molar number of furandicarboxylic acid added is less than the molar number of the initial aliphatic diamine, the resulting powder will show weak alkalinity or alkalinity.
[0056] Wherein, the grinding temperature is 0-45°C.
[0057] Wherein, when preparing pentamethylenediamine furandicarboxylate, the grinding temperature is 30-40°C.
[0058] Wherein, when preparing hexamethylenediamine furandicarboxylate, the grinding temperature is 35-45°C.
[0059] Wherein, when preparing heptyldiamine furandicarboxylate, the grinding temperature is 10-20°C.
[0060] Wherein, when preparing octanediamine furan dicarboxylate, the grinding temperature is 0-10°C.
[0061] Wherein, when preparing nonanediamine furandicarboxylate, the grinding temperature is 25-35°C.
[0062] Wherein, when preparing decanediamine furandicarboxylate, the grinding temperature is 5-15°C.
[0063] Wherein, the grinding is carried out in any of the following ways:
[0064] (i) directly grinding furandicarboxylic acid and aliphatic diamine;
[0065] (ii) furandicarboxylic acid, aliphatic diamine and a solvent are ground.
[0066] In the method (ii), the solvent can be added in various ways, such as directly adding it to the mixture in a liquid form at one time before grinding, or slowly adding it to the mortar in a liquid form multiple times during grinding, or adding it to the mortar multiple times before and during grinding. It can be added in any of the following ways, preferably slowly adding it to the mixture of aliphatic diamine and furandicarboxylic acid in a liquid form multiple times, such as the solvent is added in the method described in (ii-2) or (ii-3);
[0067] (ii-1) before grinding, the solvent is added to the mixture of furandicarboxylic acid and aliphatic diamine at one time for grinding;
[0068] (ii-2) adding a solvent during the grinding of furandicarboxylic acid and aliphatic diamine;
[0069] (ii-3) Before grinding, part of the solvent is added to the mixture of furandicarboxylic acid and aliphatic diamine for grinding, and the remaining solvent is added during the grinding process.
[0070] Wherein, the usage ratio of the aliphatic diamine to the solvent is 10-20 mmol: 0-3 mL, preferably 10-20 mmol: 0.5-3 mL.
[0071] The solvent is any one or more of methanol, ethanol, isopropanol, acetonitrile, ethyl acetate, ethyl formate, methyl acetate, butyl acetate, acetone, butanone, petroleum ether, tetrahydrofuran and dimethyl sulfoxide, or a mixed solvent of any one or more of the foregoing and water; preferably, methanol, ethanol, ethyl acetate, acetone, dimethyl sulfoxide, isopropanol, acetonitrile, or a mixed solvent of any one of the foregoing and water, or a mixed solvent of any one of the foregoing and water; different solvents can also be slowly added multiple times during the grinding process.
[0072] Wherein, when preparing pentamethylenediamine furandicarboxylate, the solvent is a mixed solution of water and ethanol, preferably, the volume ratio of water to ethanol is 1:0.5-1.5, preferably 1:1.
[0073] Wherein, when preparing hexamethylenediamine furan dicarboxylate, the solvent is ethyl acetate.
[0074] Wherein, when preparing heptyldiamine furan dicarboxylate, the solvent is a ketone compound, preferably acetone.
[0075] Wherein, when preparing octanediamine furan dicarboxylate, the solvent is an alcohol compound, preferably isopropanol.
[0076] Wherein, when preparing nonanediamine furan dicarboxylate, the solvent is dimethyl sulfoxide.
[0077] Wherein, when preparing decanediamine furan dicarboxylate, the solvent is ethyl acetate.
[0078] It should be noted that in the preparation method of the present invention, the operations for preparing different PAnF salts mainly depend on the difference in auxiliary solvent and grinding time.
[0079] When the aliphatic diamine furandicarboxylate crystals are PA5F salts, they are prepared by wet grinding crystallization, and the steps are as follows: pentamethylenediamine and furandicarboxylic acid are added to a mortar, a small amount of solvent is added before or during grinding, and grinding is performed for 5 minutes to 2 hours to obtain PA5F salt, preferably grinding for 18 to 29 minutes.
[0080] When the aliphatic diamine furandicarboxylate crystals are PA6F salts, they are prepared by dry or wet grinding crystallization, and the steps are as follows: hexamethylenediamine and furandicarboxylic acid are added to a mortar, no solvent is added during the grinding process or a solvent is added before or during the grinding process, and the grinding is performed for 10 minutes to 4 hours to obtain PA6F salt, preferably for 10 to 50 minutes.
[0081] When the aliphatic diamine furandicarboxylate crystals are PA7F salts, they are prepared by wet grinding crystallization, and the steps are as follows: adding heptanediamine and furandicarboxylic acid into a mortar, adding a small amount of solvent before or during grinding, and grinding for 10 minutes to 3 hours to obtain PA7F salt, preferably grinding for 13 to 25 minutes.
[0082] When the aliphatic diamine furandicarboxylate crystals are PA8F salts, they are prepared by wet grinding crystallization, and the steps are as follows: add octanediamine and furandicarboxylic acid into a mortar, add a small amount of solvent before or during grinding, and grind for 5 minutes to 2 hours to obtain PA8F salt, preferably grinding for 8 to 18 minutes.
[0083] When the aliphatic diamine furandicarboxylate crystals are PA9F salts, they are prepared by wet grinding crystallization, and the steps are as follows: pentamethylenediamine and furandicarboxylic acid are added to a mortar, a small amount of solvent is added before or during grinding, and grinding is performed for 10 minutes to 3 hours to obtain PA9F salt, preferably grinding for 15 to 30 minutes.
[0084] When the aliphatic diamine furandicarboxylate crystals are PA10F salts, they are prepared by wet grinding crystallization, and the steps are as follows: add decanediamine and furandicarboxylic acid into a mortar, add a small amount of solvent before or during grinding, and grind for 10 minutes to 2 hours to obtain PA10F salt, preferably grinding for 15 to 25 minutes.
[0085] It should be pointed out that in the preparation method of the present invention, in the crystallization process in the presence of an organic solvent, in order to reduce the volatilization of the organic solvent, it is possible to consider carrying out the grinding process in a low temperature environment, such as -10 to 30°C.
[0086] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0087] The present invention provides a high-purity PAnF salt crystal structure with an equal molar ratio of aliphatic diamine and furandicarboxylic acid, and provides a green, sustainable and efficient mechanochemical grinding method, which can achieve controlled crystallization results in the field of drug cocrystal construction without solvent or with a small amount of solvent. In this way, the product form is changed, the odor of aliphatic diamine is eliminated, and it is easy to transport, and the purity and stability of the polymerized monomer are improved, and the requirements of nylon polymerization on the molar ratio are met, so that it can be directly used for polymerization. At the same time, the present invention can shorten the grinding time by grinding in a specific solvent. BRIEF DESCRIPTION OF THE DRAWINGS
[0088] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0089] Figure 1 Molecular ellipsoid diagram of the smallest asymmetric unit of six crystal structures of aliphatic diamine furandicarboxylates.
[0090] Figure 2 The cell stacking diagrams of six crystal structures of aliphatic diamine furandicarboxylates.
[0091] Figure 3 The X-ray powder diffraction patterns of six crystal structures of aliphatic diamine furandicarboxylates.
[0092] Figure 4 These are six TGA-DSC graphs of aliphatic diamine furandicarboxylates. DETAILED DESCRIPTION
[0093] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0094] The detection method and instrument of the PAnF salt crystal structure of the present invention are as follows:
[0095] Single crystal X-ray diffraction to determine the crystal structure and analysis method: Take the cultured aliphatic diamine furan dicarboxylate single crystals of good quality, cut them into blocks, and use a Bruker SMART APEX single crystal diffractometer Mo Kα radiation source (graphite monochromator, The samples were irradiated and diffraction data were collected. Single crystal data were solved by direct methods in SHELXL and by full matrix least squares in F 2 The data were processed using PLATON and the crystal structure was visualized using MERCURY 3.6.
[0096] Powder X-ray diffraction: The sample was ground in an agate mortar for about two minutes, and the diffraction data were collected by powder X-ray diffractometer (Bruker D8Advance) at room temperature. The light source was Cu Kα ray with a wavelength of The tube voltage was 50 kV, the tube current was 50 mA, the scanning speed was 10° / min, and the scanning range 2θ was 5°~40°. The data were processed by JADE software and plotted by origin software.
[0097] Thermogravimetric analysis and differential scanning calorimetry (TGA-DSC): Swiss Mettler TGA / DSC 3+ was used to analyze the thermodynamic properties of the obtained bio-based nylon nF salt monomer crystalline products. Test method: Accurately weigh 5-10 mg of sample and place it in a sealed crucible, select nitrogen as the atmosphere, and heat from room temperature to 350°C at a heating rate of 5°C / min under nitrogen purge (rate of 50ml / min), and plot with origin software.
[0098] The bulk density and tap density are quantities related to the properties of the powder. In general, it is hoped that -tap density / bulk density is close to 1. Bulk density refers to the weight of a unit volume of powder under predetermined conditions, expressed as the weight per unit volume, usually in g / mL. The tap density also indicates the weight of a unit volume of powder, which is subjected to tapping or vibration under predetermined conditions in a holder of the powder. Therefore, for the same powder, its tap density is higher than the bulk density. Crystals with large bulk density and tap density tend to have a larger specific gravity, which can reflect that the crystal product is relatively thick and textured, and its stability will also be relatively good; from another perspective, products with large bulk density generally have better fluidity of particles and are also easy to store and transport.
[0099] Specifically, the measuring methods of the bulk density and tap density of the crystalline powder are as follows:
[0100] The bulk density of the granules was determined according to USP Method II (page 1914);
[0101] The tap density of the particles is measured by a FZS4-4 economical tap density tester according to GB / T 5162-2006. Specifically, the test conditions are: the vibration stroke of the beating device is 3±0.1MM, and the vibration frequency is 250±15 times per minute.
[0102] The crystalline powder of the aliphatic diamine furandicarboxylate is white or slightly yellow.
[0103] The solid or solid powder described in the present invention is an aggregate state of matter, including amorphous and crystalline.
[0104] The crystalline powder described in the present invention refers to powder with a certain degree of crystallinity, relative to amorphous powder.
[0105] The crystal described in the present invention is a solid having a clear diffraction pattern for X-rays, and its atoms or molecules are repeatedly arranged in space according to a certain regular period.
[0106] Embodiment 1:
[0107] Weigh 1.0 g (10 mmol) of pentamethylenediamine and 1.6 g of furandicarboxylic acid (10 mmol) into an agate mortar, add 1 ml of methanol before grinding, grind at 30°C-40°C for 20 min, and then stand and dry in an oven at 40°C for 24 h to obtain 1.5 g of PA5F salt powder.
[0108] The crystal structure belongs to the monoclinic system, C2 / c space group, and the unit cell parameters are α=90°, β=100.022(2)°, γ=90°,unit cell volume In the unit cell, Z=1, and in its smallest asymmetric unit, it contains 1 pentamethylenediamine cation and 1 furandicarboxylate anion. The crystal structure information is shown in Appendix 1. The results of TGA and DSC analysis are shown in Figure 4 The DSC curve shows that there is an endothermic characteristic peak at 186.8°C, which corresponds to the melting point of the PA5F salt crystal, and an endothermic characteristic peak at 262.2°C, which corresponds to the decomposition point of the crystal, indicating that the crystal has good stability. The bulk density of the obtained PA5F salt crystal is 0.49 g / cm 3 , tap density is 0.66g / cm 3 Its powder X-ray diffraction pattern is shown in the attached Figure 3 As shown, the diffraction angle 2θ±0.1 is expressed as follows.
[0109] Table 2 X-ray powder diffraction characteristic spectrum of PA5F salt crystals
[0110]
[0111] Embodiment 2:
[0112] Weigh 2.6 g (25 mmol) of pentamethylenediamine and 3.1 g (20 mmol) of furandicarboxylic acid and place them in a fully automatic sample rapid grinder-24L (Jingxin JXFSTPRP-24L). Add 0.5 ml of water before grinding. Under the condition of 30℃-40℃, the power is 70HZ, run for 70S, stop for 20S, repeat 25 times, and then stand and dry in a 40℃ oven for 24h to obtain 3.9 g of PA5F salt powder.
[0113] The crystal structure belongs to the monoclinic system, C2 / c space group, and the unit cell parameters are α=90°, β=100.022(2)°, γ=90°,unit cell volume Z = 1 in the unit cell, and in its smallest asymmetric unit, it contains 1 pentamethylenediamine cation and 1 furandicarboxylate anion. The packing density of the obtained PA5F salt crystal is 0.52 g / cm 3 , tap density is 0.71g / cm 3 .
[0114] Embodiment 3:
[0115] Weigh 2.6 g (25 mmol) of pentamethylenediamine and 3.1 g (20 mmol) of furandicarboxylic acid and place them in a fully automatic sample rapid grinder-24L (Jingxin JXFSTPRP-24L). Add 0.5 ml of water and 0.5 ml of ethanol before grinding. Under the condition of 30°C-40°C, the power is 70 Hz, run for 70 seconds, stop for 20 seconds, repeat 15 times, and then stand and dry in an oven at 40°C for 24 hours to obtain 4 g of PA5F salt powder.
[0116] Embodiment 4:
[0117] Weigh 1.7 g (15 mmol) of hexamethylenediamine and 2.6 g (17 mmol) of furandicarboxylic acid and place them in a fully automatic sample rapid grinder-24L (Jingxin JXFSTPRP-24L). Add 1 ml of ethanol before grinding. Under the condition of 35°C-45°C, the power is 60 Hz, run for 60 seconds, stop for 15 seconds, repeat 20 times, and then stand and dry in an oven at 40°C for 12 hours to obtain 3.4 g of PA6F salt powder.
[0118] The crystal structure belongs to the monoclinic system, P21 / c space group, and the unit cell parameters are α=90°, β=108.538(3)°, γ=90°,unit cell volume The unit cell has Z=4, and in its smallest asymmetric unit, it contains 1 hexamethylenediamine cation and 1 furandicarboxylate anion. The crystal structure information is shown in Appendix 1. The TGA and DSC analysis results are shown in Figure 4 It shows that there is a weight loss step at 264.2℃, which corresponds to the decomposition point of the crystal, indicating that the crystal has good stability. The bulk density of the obtained PA6F salt crystal is 0.82g / cm 3 , tap density is 0.89g / cm 3 Its powder X-ray diffraction pattern is shown in the attached Figure 3 As shown, the diffraction angle 2θ±0.1 is expressed as follows.
[0119] Table 3 X-ray powder diffraction characteristic spectrum of PA6F salt crystals
[0120]
[0121] Embodiment 5:
[0122] 1.2 g (10 mmol) of hexamethylenediamine and 1.6 g (10 mmol) of furandicarboxylic acid were weighed and placed in an agate mortar. No solvent was added during the grinding process. The mixture was ground at 35° C.-45° C. for 50 min to obtain 1.4 g of PA6F salt powder.
[0123] The crystal structure belongs to the monoclinic system, P21 / c space group, and the unit cell parameters are α=90°, β=108.538(3)°, γ=90°,unit cell volume Z=4 in the unit cell, and in its smallest asymmetric unit, it contains 1 hexamethylenediamine cation and 1 furandicarboxylate anion. The packing density of the obtained PA6F salt crystal is 0.84 g / cm 3 , tap density is 0.88g / cm 3 .
[0124] Embodiment 6:
[0125] Weigh 1.7 g (15 mmol) of hexamethylenediamine and 2.6 g (17 mmol) of furandicarboxylic acid and place them in a fully automatic sample rapid grinder-24L (Jingxin JXFSTPRP-24L). Add 0.8 ml of ethyl acetate before grinding. Under the condition of 35°C-45°C, the power is 60HZ, run for 60S, stop for 15S, repeat 10 times, and then stand and dry in an oven at 40°C for 12h to obtain 3.7 g of PA6F salt powder.
[0126] The crystal structure belongs to the monoclinic system, P21 / c space group, and the unit cell parameters are α=90°, β=108.538(3)°, γ=90°,unit cell volume Z=4 in the unit cell. In its smallest asymmetric unit, it contains 1 hexamethylenediamine cation and 1 furandicarboxylate anion. The crystal structure information is shown in Appendix 1.
[0127] Example 6-1
[0128] The same as Example 6, after the grinding temperature was changed to 0-10°C, other conditions were the same, and the PXRD patterns of the obtained products were compared and no PA6F salt substance was found.
[0129] Embodiment 7:
[0130] Weigh 1.6 g (12 mmol) of heptanediamine and 1.9 g (12 mmol) of furandicarboxylic acid into an agate mortar, add 1 ml of DMSO before grinding, grind at 10°C-20°C for 25 min, and then stand and dry in a vacuum drying oven at 40°C for 24 h to obtain 2.1 g of PA7F salt powder.
[0131] The crystal structure belongs to the monoclinic system, P21 / c space group, and the unit cell parameters are α=90°, β=105.896(3)°, γ=90°,unit cell volume The number of molecules in the unit cell is Z = 4. In its smallest asymmetric unit, it contains 1 heptanediamine cation and 1 furandicarboxylate anion. The crystal structure information is shown in Appendix 1. The results of TGA and DSC analysis are shown in Figure 4 The DSC curve shows that there is an endothermic characteristic peak at 203°C, which corresponds to the melting point of the PA7F salt crystal, and an endothermic characteristic peak at 270.8°C, which corresponds to the decomposition point of the crystal, indicating that the crystal has good stability. The bulk density of the PA7F salt crystal obtained is 0.47 g / cm 3 , tap density is 0.53g / cm 3 Its powder X-ray diffraction pattern is shown in the attached Figure 3 As shown, the diffraction angle 2θ±0.1 is expressed as follows.
[0132] Table 4 X-ray powder diffraction characteristic spectrum of PA7F salt crystals
[0133]
[0134] Embodiment 8:
[0135] Weigh 1.6 g (12 mmol) of heptanediamine and 2.5 g (16 mmol) of furandicarboxylic acid and place them in a fully automatic sample rapid grinder-24L (Jingxin JXFSTPRP-24L). Add 1.2 ml of methanol during the grinding process. Under the condition of 10℃-20℃, the power is 65HZ, run for 40S, stop for 10S, repeat 30 times, and then stand and dry in a vacuum drying oven at 40℃ for 24h to obtain 3g of PA7F salt powder.
[0136] The crystal structure belongs to the monoclinic system, P21 / c space group, and the unit cell parameters are α=90°, β=105.896(3)°, γ=90°,unit cell volume Z = 4 in the unit cell, and in its smallest asymmetric unit, it contains 1 heptanediamine cation and 1 furandicarboxylate anion. The packing density of the obtained PA7F salt crystal is 0.58 g / cm 3 , tap density is 0.62g / cm 3 .
[0137] Embodiment 9:
[0138] Weigh 1.6 g (12 mmol) of heptanediamine and 2.5 g (16 mmol) of furandicarboxylic acid and place them in a fully automatic sample rapid grinder-24L (Jingxin JXFSTPRP-24L). Add 1 ml of acetone during the grinding process. Under the condition of 10℃-20℃, the power is 65HZ, run for 40S, stop for 10S, repeat 20 times, and then stand and dry in a vacuum drying oven at 40℃ for 24h to obtain 3.2g of PA7F salt powder.
[0139] The crystal structure belongs to the monoclinic system, P21 / c space group, and the unit cell parameters are α=90°, β=105.896(3)°, γ=90°,unit cell volume Z=4 in the unit cell, and its smallest asymmetric unit contains 1 heptanediamine cation and 1 furandicarboxylate anion.
[0140] Example 9-1
[0141] The same as Example 9, except that the grinding temperature was changed to 30-40°C, and other conditions were the same, and no PA7F salt substance was found after comparing the PXRD patterns of the obtained products.
[0142] Embodiment 10:
[0143] Weigh 1.9 g (13 mmol) of octanediamine and 2 g (13 mmol) of furandicarboxylic acid into an agate mortar, add 1 ml of acetonitrile before grinding, grind at 0°C-10°C for 18 min, and then stand and dry in an oven at 40°C for 12 h to obtain 1.9 g of PA8F salt powder.
[0144] The crystal structure belongs to the monoclinic system, C2 / c space group, and the unit cell parameters are α=90°, β=127.238(6)°, γ=90°,unit cell volume The unit cell has Z=4, and in its smallest asymmetric unit, it contains 0.5 octanediamine cations and 0.5 furandicarboxylate anions. The crystal structure information is shown in Appendix 1. The TGA and DSC analysis results are shown in Figure 4The DSC curve shows two endothermic peaks starting from 243.1°C and is accompanied by weight loss on the TGA curve, indicating that melting and decomposition occurred simultaneously. The bulk density of the PA8F salt crystals obtained is 0.25 g / cm 3 , tap density is 0.3g / cm 3 Its powder X-ray diffraction pattern is shown in the attached Figure 3 As shown, the diffraction angle 2θ±0.1 is expressed as follows.
[0145] Table 5 X-ray powder diffraction characteristic spectrum of PA8F salt crystals
[0146]
[0147] Embodiment 11:
[0148] Weigh 2 g (14 mmol) of octanediamine and 1.6 g (10 mmol) of furandicarboxylic acid and place them in a fully automatic sample rapid grinder-24L (Jingxin JXFSTPRP-24L). Add 1 ml of isopropanol during the grinding process. Under the condition of 0℃-10℃, the power is 50 Hz, run for 50 seconds, stop for 15 seconds, repeat 10 times, and then stand and dry in a 40℃ oven for 12 hours to obtain 2.5 g of PA8F salt.
[0149] The crystal structure belongs to the monoclinic system, C2 / c space group, and the unit cell parameters are α=90°, β=127.238(6)°, γ=90°,unit cell volume Z = 4 in the unit cell, and in its smallest asymmetric unit, it contains 0.5 octanediamine cations and 0.5 furandicarboxylate anions. The packing density of the resulting PA8F salt crystals is 0.38 g / cm 3 , tap density is 0.44g / cm 3 .
[0150] Embodiment 12:
[0151] Weigh 2g (14mmol) of octanediamine and 1.6g (10mmol) of furandicarboxylic acid and place them in a fully automatic sample rapid grinder-24L (Jingxin JXFSTPRP-24L). Add 1ml of petroleum ether during the grinding process. Under the condition of 0℃-10℃, the power is 50HZ, run for 50S, stop for 15S, repeat 15 times, and then stand and dry in a 40℃ oven for 12h to obtain 2.6g of PA8F salt powder.
[0152] The crystal structure belongs to the monoclinic system, C2 / c space group, and the unit cell parameters are α=90°, β=127.238(6)°, γ=90°,unit cell volume Z=4 in the unit cell, and in its smallest asymmetric unit, it contains 0.5 octanediamine cations and 0.5 furandicarboxylate anions.
[0153] Example 12-1
[0154] The same as Example 12, except that the grinding temperature was changed to 15-25° C., and other conditions were the same. After comparing the PXRD patterns of the obtained products, no PA8F salt substance was found.
[0155] Embodiment 13:
[0156] Weigh 2.4 g (15 mmol) of nonanediamine and 2.3 g (15 mmol) of furandicarboxylic acid into an agate mortar, add 2 ml of acetonitrile before grinding, grind at 25°C-35°C for 30 min, and then stand and dry in a vacuum drying oven at 40°C for 24 h to obtain 3 g of PA9F salt powder.
[0157] The crystal structure belongs to the monoclinic system, Cc space group, and the unit cell parameters are α=90°, β=108.924(3)°, γ=90°,unit cell volume In the unit cell, Z=1, and in its smallest asymmetric unit, it contains 4 nonanediamine cations and 4 furandicarboxylate anions. The crystal structure information is shown in Appendix 1. The results of TGA and DSC analysis are shown in Figure 4 The DSC curve shows that there is an endothermic characteristic peak at 212.5°C, which corresponds to the melting point of the PA9F salt crystal, and an endothermic characteristic peak at 281.9°C, which corresponds to the decomposition point of the crystal. The crystal has good stability. The bulk density of the obtained PA9F salt crystal is 0.49 g / cm 3 , tap density is 0.55g / cm 3 Its powder X-ray diffraction pattern is shown in the attached Figure 3 As shown, the diffraction angle 2θ±0.1 is expressed as follows.
[0158] Table 6 X-ray powder diffraction characteristic spectrum of PA9F salt crystals
[0159]
[0160] Embodiment 14:
[0161] Weigh 2.4 g (15 mmol) of nonanediamine and 1.9 g (12 mmol) of furandicarboxylic acid and place them in a fully automatic sample rapid grinder-24L (Jingxin JXFSTPRP-24L). Add 1 ml of ethanol during the grinding process. Under the condition of 25℃-35℃, the power is 70HZ, run for 60S, stop for 10S, repeat 25 times, and then stand and dry in a vacuum drying oven at 40℃ for 24h to obtain 3.5g of PA9F salt powder.
[0162] The crystal structure belongs to the monoclinic system, Cc space group, and the unit cell parameters are α=90°, β=108.924(3)°, γ=90°,unit cell volume Z = 1 in the unit cell, and in its smallest asymmetric unit, it contains 4 nonanediamine cations and 4 furandicarboxylate anions. The packing density of the obtained PA9F salt crystals is 0.60 g / cm 3 , tap density is 0.66g / cm 3 .
[0163] Embodiment 15:
[0164] Weigh 2.4 g (15 mmol) of nonanediamine and 1.9 g (12 mmol) of furandicarboxylic acid and place them in a fully automatic sample rapid grinder-24L (Jingxin JXFSTPRP-24L). Add 0.5 ml of dimethyl sulfoxide during the grinding process. Under the condition of 25℃-35℃, the power is 70HZ, run for 60S, stop for 10S, repeat 15 times, and then stand and dry in a vacuum drying oven at 40℃ for 24h to obtain 3.7g of PA9F salt powder.
[0165] The crystal structure belongs to the monoclinic system, Cc space group, and the unit cell parameters are α=90°, β=108.924(3)°, γ=90°,unit cell volume Z=1 in the unit cell, and its smallest asymmetric unit contains 4 nonanediamine cations and 4 furandicarboxylate anions.
[0166] Example 15-1
[0167] The same as Example 15, except that the grinding temperature was changed to 0-20°C, and other conditions were the same, and no PA9F salt substance was found after comparing the PXRD patterns of the obtained products.
[0168] Embodiment 16:
[0169] Weigh 2.7 g (16 mmol) of decanediamine and 2.5 g (16 mmol) of furandicarboxylic acid into an agate mortar, add 1.5 ml of acetonitrile during the grinding process, grind at 5°C-15°C for 30 min, and then stand and dry in an oven at 40°C for 12 h to obtain 3.6 g of PA10F salt powder.
[0170] The crystal structure belongs to the monoclinic system, C2 / c space group, and the unit cell parameters are α=90°, β=124.338(6)°, γ=90°,unit cell volume The unit cell has Z=4, and in its smallest asymmetric unit, it contains 0.5 decanediaminium cations and 0.5 furandicarboxylate anions. The crystal structure information is shown in Appendix 1. The TGA and DSC analysis results are shown in Figure 4 The DSC curve shows that there is an endothermic characteristic peak at 235.3°C, which corresponds to the melting point of the PA10F salt crystal, and an endothermic characteristic peak at 270.4°C, which corresponds to the decomposition point of the crystal, indicating that the crystal has good stability. The bulk density of the obtained PA10F salt crystal is 0.53 g / cm 3 , tap density is 0.74g / cm 3 Its powder X-ray diffraction pattern is shown in the attached Figure 3 As shown, the diffraction angle 2θ±0.1 is expressed as follows.
[0171] Table 7 X-ray powder diffraction characteristic spectrum of PA10F salt crystals
[0172]
[0173] Embodiment 17:
[0174] Weigh 1.7 g (10 mmol) of decanediamine and 2.0 g (13 mmol) of furandicarboxylic acid and place them in a fully automatic sample rapid grinder-24L (Jingxin JXFSTPRP-24L), add 1.5 ml of ethanol before grinding, run at 70 Hz at 5°C-15°C, run for 60 seconds, stop for 20 seconds, repeat 25 times, then stand and dry in a 40°C oven for 12 hours to obtain 2.5 g of PA10F salt powder.
[0175] The crystal structure belongs to the monoclinic system, C2 / c space group, and the unit cell parameters are α=90°, β=124.338(6)°, γ=90°,unit cell volume Z = 4 in the unit cell, and in its smallest asymmetric unit, it contains 0.5 decanediaminium cations and 0.5 furandicarboxylate anions. The packing density of the resulting PA10F salt crystals is 0.6 g / cm 3 , tap density is 0.78g / cm 3 .
[0176] Embodiment 18:
[0177] Weigh 1.7 g (10 mmol) of decanediamine and 2.0 g (13 mmol) of furandicarboxylic acid and place them in a fully automatic sample rapid grinder-24L (Jingxin JXFSTPRP-24L). Add 0.5 ml of ethyl acetate before grinding. Under the condition of 5°C-15°C, the power is 70 Hz, run for 60 seconds, stop for 20 seconds, repeat 19 times, and then stand and dry in a 40°C oven for 12 hours to obtain 2.7 g of PA10F salt powder.
[0178] Comparative Example 1:
[0179] The preparation method refers to Example 1 in patent CN112111058A. Dissolve 2,5-furandicarboxylic acid and 1,6-hexanediamine in anhydrous ethanol at a molar ratio of 1:1, then slowly pour the 1,6-hexanediamine solution into the 2,5-furandicarboxylic acid solution. Under nitrogen protection and magnetic stirring, the reaction temperature is 50°C, and the water bath reaction is carried out for 12 hours to produce precipitation. The precipitate is cooled and filtered, and vacuum dried for 12 hours to obtain a composite salt. The obtained composite salt is in the form of white powder. After testing, the bulk density is 0.51g / cm 3 , tap density is 0.64g / cm 3 The overall crystal particles are relatively small and the texture is not strong.
[0180] Comparative Example 2:
[0181] The preparation method refers to Example 2 in patent CN111925521A. The air in the stainless steel salt-forming reactor is replaced three times by vacuuming and introducing nitrogen. Under nitrogen protection, 1 mol of bio-based monomer 2,5-furandicarboxylic acid, 1.10 mol of bio-based monomer 1,5-pentanediamine, 536 mg of phosphorous acid catalyst and 500 mL of ethanol are added to the salt-forming reactor to obtain a mixture; stirring is started to mix the above mixture evenly, the stirring speed is set to 350 rpm, and the above mixture is heated to 72°C at normal pressure and reacted for 75 minutes. After the reaction, the pH of the solution is 7.4, and a furandicarboxylic acid pentamethylenediamine salt solution with a mass fraction of 38% is obtained. It is placed in a 40°C oven for evaporation and crystallization to obtain a solid powder. The bulk density of the substance is tested to be 0.23 g / cm 3 , tap density is 0.39g / cm 3 .
[0182] Comparative Example 3:
[0183] The preparation method refers to Example 7 in patent CN111925521A. The air in the stainless steel salt-forming reactor is replaced three times by vacuuming and introducing nitrogen. Under nitrogen protection, 1 mol of bio-based monomer 2,5-furandicarboxylic acid, 1.0 mol of bio-based monomer 1,10-decanediamine, 32.8 mg of phosphorous acid catalyst and 400 mL of dimethylformamide are added to the salt-forming reactor to obtain a mixture; stirring is started to mix the above mixture evenly, the stirring speed is set to 500 rpm, and the above mixture is heated to 120°C at normal pressure and reacted for 140 minutes. After the reaction is completed, the precipitation is cooled and centrifuged, and the obtained precipitate is washed several times with dimethylformamide and deionized water to obtain furandicarboxylic acid decanediamine salt. After testing, the bulk density is 0.29 g / cm 3 , tap density is 0.37g / cm 3 The overall crystal particles are relatively small.
[0184] The humidity stability of PA5F salt, PA6F salt, PA7F salt, PA8F salt, PA9F salt and PA10F salt as well as the products in Comparative Examples 1, 2 and 3 at relative humidity of 98%, 76%, 67%, 43%, 32% and 0% respectively was tested, and the results are shown in Table 8. Under high humidity conditions of 98% relative humidity, several crystals showed certain hygroscopic behavior. Compared with the comparative example products, the humidity stability of the three crystal products prepared in this patent was better.
[0185] Table 8 Humidity stability test
[0186] 0% 32% 43% 67% 76% 98% PA5F Salt 0% 0% 0% 0% 48.5% 250.1% PA6F Salt 0% 0% 0% 13% - - PA7F Salt 0% 0% 0% 0% 0% 117.4% PA8F Salt 0% 0% 0% 0% 0% 148.7% PA9F Salt 0% 0% 0% 0% 0% 151.5% PA10F Salt 0% 0% 0% 0% 20.8% 180.1% Comparative Example 1 0% 0% 0% 18% - - Comparative Example 2 0% 0% 0% 16.5% 70.3% 294.5% Comparative Example 3 0% 0% 0% 0% 6.1% 205.4%
[0187] The present invention provides a green and environmentally friendly method for preparing bio-based nylon nF material monomers and a series of aliphatic diamine furandicarboxylates, and their crystal structures. Compared with the traditional anti-solvent and cooling crystallization methods, the present invention makes the diamine and the dibasic acid into a salt form by grinding, and the product is presented in the form of crystals with an equal molar ratio of aliphatic diamine and furandicarboxylic acid, which reduces the amine volatilization loss during the polymerization process and ensures the molar ratio of the raw materials. The product is more stable and can be directly used for polymerization, and has advantages in transportation, use, storage and quality.
[0188] There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be considered as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. A method for preparing an aliphatic diamine furan dicarboxylate of formula I, characterized in that: The method comprises grinding a mixture containing an aliphatic diamine and furandicarboxylic acid to crystallize an aliphatic diamine furandicarboxylic acid salt; The salt is separated from the mixture and dried to obtain; n is any integer selected from 5-10.
2. The method for preparing aliphatic diamine furandicarboxylate according to claim 1, characterized in that: The tap density / bulk density of the aliphatic diamine furandicarboxylate is 1.0 to 1.25, preferably 1.05 to 1.
20.
3. The aliphatic diamine furandicarboxylate according to claim 1, characterized in that: When n=6, the diamine furan dicarboxylate is hexamethylenediamine furan dicarboxylate, and the crystal structure of the hexamethylenediamine furan dicarboxylate belongs to the monoclinic system, the P21 / c space group, and the unit cell parameters are α=90°, β=108.538(3)°, γ=90°,unit cell volume Z=4 in the unit cell, and contains 1 hexamethylenediamine cation and 1 furandicarboxylate anion in its smallest asymmetric unit; preferably, the hexamethylenediamine furandicarboxylate has a diffraction pattern as shown in the PA6F salt curve in FIG3 using CuKα rays as characteristic X-rays for diffraction analysis.
4. The aliphatic diamine furandicarboxylate according to claim 1, characterized in that: When n=7, the diamine furan dicarboxylate is heptyl diamine furan dicarboxylate, and the crystal structure of the heptyl diamine furan dicarboxylate belongs to the monoclinic system, the P21 / c space group, and the unit cell parameters are α=90°, β=105.896(3)°, γ=90°,unit cell volume Z=4 in the unit cell, and contains 1 heptanediamine cation and 1 furandicarboxylate anion in its smallest asymmetric unit; preferably, the heptanediamine furandicarboxylate has a diffraction pattern as shown in the PA7F salt curve in FIG3 using CuKα rays as characteristic X-rays for diffraction analysis.
5. The aliphatic diamine furandicarboxylate according to claim 1, characterized in that: When n=8, the diamine furan dicarboxylate is octanediamine furan dicarboxylate, and the crystal structure of the octanediamine furan dicarboxylate belongs to the monoclinic system, the C2 / c space group, and the unit cell parameters are α=90°, β=127.238(6)°, γ=90°,unit cell volume Z=4 in the unit cell, and contains 0.5 octanediamine cations and 0.5 furandicarboxylate anions in its smallest asymmetric unit; preferably, the octanediamine furandicarboxylate has a diffraction pattern as shown in the PA8F salt curve in FIG3 using CuKα rays as characteristic X-rays for diffraction analysis.
6. The aliphatic diamine furandicarboxylate according to claim 1, characterized in that: When n=9, the diamine furandicarboxylate is nonanediamine furandicarboxylate, and the crystal structure of the nonanediamine furandicarboxylate belongs to the monoclinic system, the Cc space group, and the unit cell parameter is α=90°, β=108.924(3)°, γ=90°,unit cell volume Z=1 in the unit cell, and contains 4 nonanediamine cations and 4 furandicarboxylate anions in its smallest asymmetric unit; preferably, the nonanediamine furandicarboxylate has a diffraction pattern as shown in the PA9F salt curve in FIG3 using CuKα rays as characteristic X-rays for diffraction analysis.
7. The preparation method according to claim 1, characterized in that: The grinding temperature is 0-45°C; preferably, when preparing pentamethylenediamine furan dicarboxylate, the grinding temperature is 30-40°C; preferably, when preparing hexamethylenediamine furan dicarboxylate, the grinding temperature is 35-45°C; preferably, when preparing heptamethylenediamine furan dicarboxylate, the grinding temperature is 10-20°C; preferably, when preparing octanediamine furan dicarboxylate, the grinding temperature is 0-10°C; preferably, when preparing nonanediamine furan dicarboxylate, the grinding temperature is 25-35°C; preferably, when preparing decanediamine furan dicarboxylate, the grinding temperature is 5-15°C.
8. The preparation method according to claim 1, characterized in that: The grinding is carried out in any of the following ways: (i) directly grinding furandicarboxylic acid and aliphatic diamine; (ii) grinding furandicarboxylic acid, an aliphatic diamine and a solvent; Preferably, in method (ii), the solvent is added in any of the following ways: (ii-1) adding the solvent to the mixture of furandicarboxylic acid and aliphatic diamine at one time before grinding and grinding; (ii-2) adding the solvent during the grinding process of furandicarboxylic acid and aliphatic diamine; (ii-3) adding part of the solvent to the mixture of furandicarboxylic acid and aliphatic diamine before grinding and grinding, and adding the remaining solvent during the grinding process; More preferably, in method (ii), the solvent is added in the method described in (ii-2) or (ii-3).
9. The preparation method according to claim 8, characterized in that: The usage ratio of the aliphatic diamine to the solvent is 10-20 mmol:0-3 mL, preferably 10-20 mmol:0.5-3 mL.
10. The preparation method according to claim 8, characterized in that: The solvent is any one or more of methanol, ethanol, isopropanol, acetonitrile, ethyl acetate, ethyl formate, methyl acetate, butyl acetate, acetone, butanone, petroleum ether, tetrahydrofuran and dimethyl sulfoxide, or a mixed solvent of any one or more of the foregoing and water; preferably, when preparing pentamethylenediamine furan dicarboxylate, the solvent is a mixed solution of water and ethanol, preferably a volume ratio of water to ethanol of 1:0.5-1.5, preferably 1:1; preferably, when preparing hexamethylenediamine furan dicarboxylate, the solvent is ethyl acetate; preferably, when preparing heptamethylenediamine furan dicarboxylate, the solvent is a ketone compound, preferably acetone; preferably, when preparing octanediamine furan dicarboxylate, the solvent is an alcohol compound, preferably isopropanol; preferably, when preparing nonamethylenediamine furan dicarboxylate, the solvent is dimethyl sulfoxide; preferably, when preparing decanediamine furan dicarboxylate, the solvent is ethyl acetate.
Citation Information
Patent Citations
Preparation method of nylon salt
CN105777553A
Improved process of producing heat resistant nylon salt
CN1887841A
High-temperature-resistant nylon preparation method
CN109575276A
Full-bio-based polyamide and preparation method thereof
CN111925521A
Preparation method of furandicarboxylic acid diamine polymer
CN112111058A